Serum proteomic analysis of melanoma patients with immunohistochemical profiling of primary melanomas and cultured cells: Pilot study - Kučera, Jan; Strnadová, Karolína; Dvořánková, Barbora; Lacina, Lukáš; Krajsová, Ivana; Štork, Jiří; Kovářová, Hana; Skalníková, Helena Kupcová; Vodička, Petr; Motlík, Jan; Dundr, Pavel; Smetana, Karel; et al. (Oncology reports, 2019)
The steadily increasing incidence of malignant melanoma (MM) and its aggressive behaviour makes this tumour an attractive cancer research topic. The tumour microenvironment is being increasingly recognised as a key factor in cancer biology, with an impact on proliferation, invasion, angiogenesis and metastatic spread, as well as acquired therapy resistance. Multiple bioactive molecules playing cooperative roles promote the chronic inflammatory milieu in tumours, making inflammation a hallmark of cancer. This specific inflammatory setting is evident in the affected tissue. However, certain mediators can leak into the systemic circulation and affect the whole organism. The present study analysed the complex inflammatory response in the sera of patients with MM of various stages. Multiplexed proteomic analysis (Luminex Corporation) of 31 serum proteins was employed. These targets were observed in immunohistochemical profiles of primary tumours from the same patients. Furthermore, these proteins were analysed in MM cell lines and the principal cell population of the melanoma microenvironment, cancer‑associated fibroblasts. Growth factors such as hepatocyte growth factor, granulocyte‑colony stimulating factor and vascular endothelial growth factor, chemokines RANTES and interleukin (IL)‑8, and cytokines IL‑6, interferon‑α and IL‑1 receptor antagonist significantly differed in these patients compared with the healthy controls. Taken together, the results presented here depict the inflammatory landscape that is altered in melanoma patients, and highlight potentially relevant targets for therapy improvement.
Keywords: nádorové biomarkery; nádorové buněčné linie; chemokiny; Biomarkers, Tumor; melanom; lidé; Blood Proteins; senioři nad 80 let; Cell Line, Tumor; senioři; Proteomics; mužské pohlaví; Female; Adult; fibroblasty asociované s nádorem; Pilot Projects; Cancer-Associated Fibroblasts; Male; krevní proteiny; ženské pohlaví; dospělí; Aged, 80 and over; Case-Control Studies; proteomika; Aged; Chemokines; Melanoma; Prognosis; Humans; lidé středního věku; pilotní projekty; Middle Aged; studie případů a kontrol; prognóza